Dendrimers-Based Drug Delivery System: A Novel Approach in Addressing Parkinson's Disease - Michaella B. Ordonio; Randa Mohammed Zaki; Amal Ali Elkordy (MDPI AG, 2022)
Parkinson's disease (PD) is a progressive neurodegenerative disease that is characterized by the loss of dopamine. Since dopamine has trouble entering the blood-brain barrier, the utilization of dendrimers and other nanomaterials is considered for conjugating the neurotransmitter and other PD drugs. Dendrimers are three-dimensional, hyper-branched structures that are categorized into several generations. Alpha-synuclein (ASN) is the protein involved in regulating dopaminergic functions and is the main aggregate found inside Lewy bodies. Different types of dendrimers have shown efficacy in disrupting the formation of unstable beta structures of ASN and fibrillation. The conjugation of PD drugs into nanomaterials has elicited a prolonged duration of action and sustained release of the drugs inside the BBB. The objectives of this study are to review the applications of a dendrimer-based drug delivery system in addressing the root cause of Parkinson's disease and to emphasize the delivery of anti-Parkinson's drugs such as rotigotine, pramipexole and dopamine using routes of administration other than oral and intravenous.